Geoffrey of Monmouth : the history of the kings of Britain : an edition and translation of De gestis Britonum (Historia regum Britanniae) - Geoffrey, of Monmouth, Bishop of St. Asaph, 1100?-1154 (Arthurian studies, 2007)
Written in the 1130s, Geoffrey's imaginative history of the Britons from Brutus to Cadwallader, and the first to recount the woes of Lear and the glittering career of Arthur, rapidly became a bestseller. An ideal text for scholars, this is a reprint of the Latin text with a facing English translation.